De onde vem minha força : um estudo sobre a influência da religiosidade dos/das cuidadores/as de pacientes com transtornos mentais - Galiza, Cinthia Jaqueline Rodrigues Bezerra (2010)
Speaking of the theme religiosity meant to work with a theme that has brought broad, intricate and dense concepts. However, perhaps because it was a large subject, it was interesting to be studied because it presented itself as a subject that did not come to an end. And the approach on the issue of mental health in a new look, from the psychiatric reform, has brought inherent discussions to human beings, who long ago were seen as animals, unthinking beings, with no desire and /or even without the right to life. The new approved federal legislation of number 10,216 on April 6th 2001 tries to come to effect and strives all the time to show that treatment for people who have mental illness can be different. The act gives specifications about the protection and the rights of people with mental disorders and redirects the care model of mental health mentioning the involvement of family and society to treat these patients with mental disorders. The experience and religious practice in this context brought a real breadth of the concept of illness and being in the world with social relations. This developed activity had as the general objective: identify whether the religiosity of relatives/caregivers of patients with mental illness could influence the treatment offered by the substitute service of mental health in the city of João Pessoa / PB, in particular at Centro de Atenção Psicossocial Infanto Juvenil Cirandar (Juvenile Psychosocial Care Center). This was an exploratory study of qualitative and quantitative nature. 36 people were interviewed, with women comprising 86.1% and men 13.9%, aged between 22 and 65 years old. It was found that the majority of respondents belonged to the black population with a percentage of 61.1% and with low educational level. Regarding the religious profile, it was revealed a high incidence of catholics and protestants. For data collection, the used instruments were: a semi-structured social, cultural and religious questionnaire and the Religious Attitude Scale. For further understanding on the issue of the influence of religiosity a focus group was conducted with caregivers of the patients who were diagnosed with mental disorders. The survey results met the proposed objectives of the work, which allowed the understanding, through the data collected, that most of the participants expressed that religion is not only present in their daily lives, but also influenced in their decision-making and behavior towards life. These results showed that 66% of respondents showed that religion influenced their decisions on their behavior. And a percentage of 89%, indicated that relatives/caregivers felt attached to a 'Higher Being'. Therefore, this study aimed to guide and expand the horizons for the importance that religion, and religiosity had on the lives of caregivers of patients with mental disorders, and showed that the religiosity caregivers presented in their speeches, besides giving them comfort, maturing and a knowledge of how to deal better with the storms of life, also gave them the ability to take better care of their sons and daughters. Thus, the disposition or tendency to religion or the sacred things of caregivers demonstrated its influence on the treatment of their relatives who were diagnosed with mental disorder.